Diagnosa Penyakit Demam Berdarah Menggunakan Metode Cased Base Reasoning (CBR) - Shela Andini; Rahmadani Rahmadani; Siswan Syahputra (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2025)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by the dengue virus and transmitted through the bite of Aedes aegypti mosquitoes. In 2023, 48 cases of DHF were reported in the Kebun Lada Public Health Center area, reflecting a high incidence rate and limited medical resources in managing the cases. This situation emphasizes the need for an alternative solution that can support a fast and accurate diagnostic process. This study aims to develop an expert system for diagnosing DHF using the Case-Based Reasoning (CBR) method. CBR functions by comparing the symptoms experienced by patients with previous cases stored in the knowledge base, thereby producing relevant diagnostic recommendations. The proposed system is implemented as a web-based application using PHP as the programming language and MySQL as the database management system. The expected outcomes of this study are to assist medical personnel in reducing diagnostic time, improving the accuracy of decision-making, and increasing the effectiveness of health services in primary healthcare facilities. In addition, the system is designed to provide wider access for the community to recognize early symptoms of DHF, which can contribute to preventive actions and reduce the risk of severe complications. Thus, the developed expert system has the potential to become a practical solution to overcome the shortage of medical personnel and enhance public health awareness.